The Prognostic Value of Preoperative Total Cholesterol in Surgically Treated Oral Cavity Cancer - Yao-Te Tsai; Ming-Hsien Tsai; Adarsh Kudva; Andrea De Vito; Chia-Hsuan Lai; Chun-Ta Liao; Chung-Jan Kang; Yuan-Hsiung Tsai; Cheng-Ming Hsu; Ethan I. Huang; Geng-He Chang; Ming-Shao Tsai; et al. (Biomedicines)
Background: With growing evidence linking lipid profile changes to tumor development and cancer prognosis, we investigated the prognostic significance of preoperative serum total cholesterol (TC) levels in patients with oral cavity squamous cell carcinoma (OSCC) undergoing surgical treatment. Methods: We conducted a retrospective observational study involving 310 patients with primary OSCC who received surgery at our hospital from January 2009 to December 2018. Receiver operating characteristic curve analysis was performed to determine the optimal preoperative TC cutoff value, with the Youden Index employed as the optimization criterion to maximize the sum of sensitivity and specificity. Variables with p < 0.1 in the univariable analysis were included in the multivariable Cox regression model, and stepwise selection was used to identify the optimal subset of prognostic factors for overall survival (OS) and disease-free survival (DFS). Results: An optimal TC cutoff of 157 mg/dL was established. Patients with TC < 157 mg/dL exhibited significantly lower 5-year rates of OS and DFS (p < 0.001 and p = 0.006, respectively). Multivariable analysis confirmed that TC < 157 mg/dL represented an independent prognostic factor for reduced OS and DFS rates. Subgroup analyses reinforced the consistent prognostic significance of TC. We also constructed a nomogram (concordance index: 0.74) to provide personalized OS predictions, enhancing the clinical utility of TC. Conclusions: Preoperative TC appears to be a significant prognostic factor for OS and DFS after OSCC surgery. Routine TC assessment facilitates the development of nomograms for personalized survival predictions, supports clinicians in tailoring treatment strategies, and guides nutritional or metabolic interventions to enhance patient outcomes. Further multicenter prospective studies are needed to validate our findings.